THE INFLUENCE OF GREEN MARKETING ON DECISION PURCHASING ECO SOUVENIR WITH PURCHASE INTENTION AS AN INTERVENING VARIABLE AT SUGAR SOUVENIR - Firdilla Qonita Firodiyarobbi (Green Publisher, 2023)
From the analysis and discussion, based on existing business problems to see the extent of the success of green marketing after one year of being carried out by Sugar Souvenirs, this study aims to analyze the effect of Green Marketing on purchasing decisions to buy environmentally friendly souvenirs with buying interest as an intervening variable on Souvenirs Sugar This study uses qualitative methods with data analysis techniques using literature study. From this study, it can be concluded as follows: Green Marketing has a significant effect on buyer interest by 65% (the indicator includes quite a lot). This means that the higher the green marketing value, the higher the public's interest in buying eco souvenirs at Sugar Souvenirs. Moreover, the Green Marketing and Purchase Intention variables contribute to the Purchasing Decision Variable by 59.7% (the indicators include sufficient numbers). So consumer interest is more significant than consumer decisions to buy.